Hippocampal activation in patients with mild cognitive impairment is necessary for successful memory encoding. Issue 8 (7th February 2007) - Kircher, Tilo T; Weis, Susanne; Freymann, Katrin; Erb, Michael; Jessen, Frank; Grodd, Wolfgang; Heun, Reinhard; Leube, Dirk T
Abstract : Background: Episodic memory enables us to consciously recollect personally experienced past events. Memory performance is reduced in patients with mild cognitive impairment (MCI), an at-risk condition for Alzheimer's disease (AD). Patients and methods: We used functional MRI (fMRI) to compare brain activity during memory encoding in 29 healthy elderly subjects (mean age 67.7 (SD 5.4) years) and 21 patients with MCI (mean age 69.7 (SD 7.0) years). Subjects remembered a list of words while fMRI data were acquired. Later, they had to recognise these words among a list of distractor words. The use of an event related paradigm made it possible to selectively analyse successfully encoded items in each individual. We compared activation for successfully encoded words between healthy elderly subjects and patients with MCI. Results: The main intergroup difference was found in the left hippocampus and surrounding medial temporal lobe (MTL) regions for the patients with MCI compared with healthy subjects during successful encoding. Conclusion: These results suggest that in patients with MCI, an increase in MTL activation is necessary for successful memory encoding. Hippocampal activation may help to link newly learned information to items already stored in memory. Increased activation in MTL regions in MCI may reflect a compensatory response to the beginning of AD pathology.